Association of TCF7L2 rs7903146 TT Genotype with Dyslipidemia in Type 2 Diabetes: A Case–Control Study in Pakistani Patients: Association of TCF7L2 rs7903146 TT Genotype with Dyslipidemia in Type 2 Diabetes - Azhar, Shazia; Farrukh, Ghazala Masood; Khalid, Zurqa; Theba, Fareha Kashan; Mughal, Sikander Adil; Siddiqui, Muhammad Khalid (Pakistan Journal of Health Sciences, 2026)
Type 2 diabetes is often accompanied by dyslipidemia, which markedly increases cardiovascular risk. Genetic factors, particularly the TCF7L2 rs7903146 variant, have been implicated in alterations in glucose and lipid metabolism in T2DM. Objectives: To assess the association between dyslipidemia and the TCF7L2 rs7903146 polymorphism in patients with T2DM as compared to healthy controls. Methods: In Karachi, Pakistan, 100 T2DM patients and 100 age- and sex-matched healthy controls participated in case-control research. Blood samples obtained during fasting were examined for cholesterol and glucose levels. PCR-RFLP was used to genotype TCF7L2 rs7903146, and sequencing was used to confirm the results. Associations (p<0.050) were assessed using logistic regression and ANOVA. Results: TT genotype and T allele frequencies were greater in T2DM patients than in controls (p<0.010). Hence, genotype carriers had significantly higher triglycerides, total cholesterol, and LDL-C levels, and lower HDL-C levels. Multivariate logistic regression demonstrated that the TT genotype independently predicted dyslipidemia. Conclusions: The TCF7L2 rs7903146 TT genotype is strongly associated with dyslipidemia in T2DM patients and may assist in risk stratification and personalized management planning.